STE-based encrypted relational database scheme with reduced leakages - SU Yuchen; MA Changshe (网络与信息安全学报)
Recently, the concept of partially precomputed indexing for Structured query language (SQL) join (PpSj), which was predicated on structured encryption, has been introduced. This approach employed partial precomputed index join and hash filter set technology to facilitate efficient execution of join queries and Boolean queries. However, the scheme has encountered some limitations, primarily characterized by excessive information leakage during the execution of Boolean queries and an inability to support range queries. To resolve these issues, an enhanced relation database encryption scheme, termed multi-function encrypted database (MFEDB), was proposed. This scheme incorporated a hybrid filter technique derived from the PpSj scheme, integrating two filtering methods. It aimed to minimize the information leakage associated with Boolean queries, expand the subset of supported SQL queries to include equivalent queries, join queries, Boolean queries, and range queries, and balance the trade-off between the server's storage costs and the communication overhead between the client and the server.